Follicular helper-like γδ T cells promote plasma cell differentiation in Behçet’s disease - Mohammed, Sahar Shaaban; Alkhalifah, Abdullah Khalifah S.; Mirza, Rahilah; Okinedo, Sarah-Pristine Omoefe; Inampudi, Rani Aishwarya; Bibi, Azimoon; Senusi, Amal; Pardieu, Claire; McCarthy, Neil E.; Fortune, Farida; Flores-Borja, Fabian (Frontiers in Immunology, 2026)
ObjectivesBehçet’s disease (BD) is a systemic vasculitis characterized by recurrent oral and genital ulcers. The disease can manifest diverse phenotypes -such as mucocutaneous, ocular BD- with an uncertain role for autoantibodies in disease pathogenesis. Altered γδT-cell and B-cell phenotypes have been widely reported in BD, but it remains unknown whether these lineages can interact to promote autoantibody production.MethodsThis study included 75 patients with a BD diagnosis, alongside 41 healthy control (HC) volunteers. We performed ex vivo flow-cytometric profiling of blood γδT and B cells, established a cell culture system to investigate plasma cell generation in vitro, and quantified anti-HSP60 autoantibody levels in BD and HC participants’ serum and cell culture supernatants.ResultsBD patients with active disease displayed a significant increase in the frequency of cells CXCR5+PD-1+ Vδ2 T cells resembling a follicular helper-like functional state. Upon stimulation, Vδ2 T cells from BD patients showed increased expression of ICOS and CXCR5, induced significant B cell proliferation, and promoted differentiation of plasma cells in vitro. Cultures of cells from BD patients contained increased levels of multiple cytokines that can support plasma cell differentiation (IL-4, IL-10, IL-17, CXCL13, TNF-α, IFN-γ). Anti-HSP60 autoantibodies were significantly enriched in blood serum from BD patients with active disease as well as the supernatants of patient-derived cell cultures compared to the healthy volunteer cell cultures.ConclusionOur findings suggest that γδT cells may enhance B-cell differentiation into antibody-producing plasma cells in BD patients with mucocutaneous and ocular clinical phenotypes.